Manajemen Sarana dan Prasarana Pendidikan Islam untuk Meningkatkan Efektivitas Pembelajaran di Pesantren Miftahul Ulum Subang - Iyus Tsaury; Mulyawan Safwandy Nugraha (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to analyze the management of educational facilities and infrastructure planning at Pesantren Miftahul Ulum Subang and its contribution to learning effectiveness. The research employed a qualitative approach with a case study design, using in-depth interviews, observations, and document analysis involving 19 participants, including the boarding school leader, teachers, students, and facilities managers. Data were analyzed thematically to identify patterns of facilities management and their impact on the learning process. The findings indicate that the needs analysis for facilities is not yet systematic and largely relies on informal reports. Facilities procurement is carried out gradually based on priority needs and available financial resources. Several facilities are underutilized due to the absence of standard operational procedures and limited supervision. The study also shows that the quality of facilities has a direct influence on learning effectiveness by enhancing classroom comfort and supporting instructional methods. It is concluded that structured and data-driven facilities planning is essential for improving the quality of learning in Islamic boarding schools.